American Fatherhood : A History - Martschukat, Jürgen (Book collections on Project MUSE., 2019)
Explores the surprising diversity of fathers and fatherhood throughout American history and society The nuclear family has been endlessly praised as the bedrock of American society, even though there has rarely been a time in history when a majority of Americans lived in such families. This book deconstructs the myth of the nuclear family by presenting the rich diversity of family lives in American history from the American Revolution to the twenty-first century. To tell this story, Jürgen Martschukat focuses on fathers and their relations to families and American society. Using biographical close-ups of twelve different characters, each embedded in historical context, American Fatherhood provides a much more realistic picture of how fatherhood has been performed within different kinds of families. Each protagonist covers a crucial period or event in American history, presents a different family constellation, and makes a different argument with regard to how American society is governed through the family.